Viabilidade econômica do aproveitamento energético da serragem na bacia hidrográfica do Rio Pardo - Dessbesell, Luana (2014)
The utilization of biomass to generate energy has been discussed as an alternative to supply worldwide demand. The use of forest residues stands out as a renewable source of energy. The utilization of forest residues such as sawdust to produce pellets brings advantages if compared to the original form of the residue s usage. The pellets have a higher energy per volume unit due to lower moisture content and compression process by which the waste is subjected. Therefore, this study discusses environmental and social aspects and an economic evaluation of pellets production in the Hydrographic Basin of Rio Pardo, while seeking for complementary alternatives to firewood used in Tobacco curing. The volume of wood processed and the number of sawmills were used to estimate the amount in tons of sawdust. Samples of sawdust were collected and the chemical composition and immediate were analyzed to characterize it. As economic evaluation criterion used the NPV, IRR, CMPR, Marginal Cost and Break-even Point. The energy density parameter was used to compare the use of pellets and firewood in tobacco curing. The daily amount of sawdust available was estimated in 69.82 tons, which can produce 11,733.12 tons of pellets each year. A financial overview demonstrated the viability of the investment showing NPV results at R$ 4.72 million and IRR 34.59% over a 10 year s cash flow budget with a discount rate of 10.9% a year. The Average Cost came to R$ 153.77 a ton, biomass and depreciation were the main partakers in this cost. If the availability of biomass improves the pellets factory can increase the number of work shifts operations and the amount produced, turning it a more attractive investment. The Marginal Cost was R$ 2.66 million a year and the Break-even Point was 5444.4 tones each year. In the Tobacco curing process pellets provide a biomass economy of 82.66% when they replace sawdust and 45.60% when firewood. In this scenario the use of pellets for Tobacco curing reduce 16.19% of the firewood purchased from outside of Hydrographic Basin and save 33.8 thousand cubic meters of firewood each year. In the Hydrographic Basin of Rio Pardo pellets utilization will bring operational benefits to Tobacco farmers in the curing process. The production of pellets in the Hydrographic Basin of Rio Pardo is sustainable because it is economic social and environmental viable.